Truth and deception in Ayacucho myths - Ansión, Juan (1982)
The Andean mythical discourse has an internal logic that must be appreciated and known. It has the coherence of a language that expresses a lived reality. Reciprocity is one of the guiding principles of the peasant's economic and social life: it is also a central element of Andean mythical stories. If social life, particularly in the Andes, presupposes respect for the rules of reciprocity, breaking with them leads to separation from society, reduces to the animal state and to the world of the night and anticulture.